Genetic diversity of Azotobacter strains isolated from various soils of Poland - Kozieł, Monika; Gałązka, Adam; Martyniuk, Stefan (Polish Journal of Agronomy, 2024)
Free living nitrogen fixing bacteria belonging to the genus Azotobacter are microorganisms commonly occurring in soil. The genus Azotobacter includes 8 species, with Azotobacter chroococcum most commonly inhabiting many soils all over the world. In this study, 56 strains were isolated from various soils of Poland, using dilution-pour plates method. Restriction analysis of the bacterial Internal Transcribed Spacer (ITS) region was used for characterization and differentiation of the isolated strains. Restriction analysis of ITS region indicated that the studied isolates were not identical. Of the 56 tested strains, 36 were characterized by the same genotype in ITS-PCR/RFLP analyzes as the reference strains A. chroococcum DSM 281 and DSM 2286. For molecular identification of the isolates, the 16S rRNA gene was amplified using 27f and 1495r primers and PCR products were sequenced at Genomed S.A. in Warsaw. The 16S rRNA gene sequence analyses of the studied strains showed 98% to 100% similarity with Azotobacter chroococcum type strain deposited in Gen Bank database. These results indicate that the analyzed isolates from Polish soils belong to one species, namely Azotobacter chroococcum.